Strukturalisasi Takwil Dalam Tafsir Ayat MutasyÄbihÄt: Studi Atas Kitab al-TafsÄ«r Al-MunÄ«r Karya Wahbah Al-ZuÄ¥aili - Mala, Fiki Khoirul; Ramadhan, Suci (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Structuralization of Takwil in The Interpretation of The MutasyÄbihÄt Verse: Study of the Book of al-TafsÄ«r Al-MunÄ«r by Wahbah Al-ZuÄ¥aili The interpretation of al-Qurâ€™an as a tool in explaining Islam needs to be interpreted comprehensively. Combining the understanding of structuralization in the interpretation process is one of the efforts used by many interpreters of the Qurâ€™an to interpret the verses of the Qurâ€™an, such as Wahbah al-ZuÄ¥aili. He is one of the interpreters who pays attention to the process of interpreting mutasyÄbihÄt verses in his work al-TafsÄ«r al-MunÄ«r. This study aims to analyze the process of structuralization of takwÄ«l used by Wahbah al-ZuÄ¥aili for the mutasyÄbihÄt verses in the book al-TafsÄ«r al-MunÄ«r. This is qualitative research with a linguistic approach that includes text and context study. The main data used is al-TafsÄ«r al-MunÄ«r and supported by other books and scientific literature. Then, data were analyzed using content analysis. The study indicates that Wahbah al-ZuÄ¥aili in doing takwÄ«l on mutasyÄbihÄt verses in al-TafsÄ«r al-MunÄ«r pays great attention to the use of grammatical language combined with the meaning of the verse so as to produce new meanings that are in accordance with the needs of society at that time and modern society today. In addition, the incorporation of this understanding of structuralization has been able to break the monotony qurâ€™anic interpretation today.